A study on biomass-fueled stoves - Cokorda Prapti Mahandari; Bhattacharya, Sribas C.; Kumar, Sivanappan; Surapong Chiraratananon; Higher Education Project, Ministry of Education and Cultural, Indonesia (Bangkok : Asian Institute of Technology, 1997)
An extensive review of literature on improved cookstove has been carried out. Based on the review, an improved ricehusk cookstove, the Philippines ricehusk cookstove was selected for experimental study. With the overall efficiency about 20 %, Philippines ricehusk cookstove can be ignited easily and quickly without noticeable smoke. It is more suitable for a single batch and short period of operation. Based on the experience with this stove a scaled-up institutional stove was designed and tested. Stove Model I has similarities with the Philippines ricehusk cookstove in terms of ease and quick starting. Overall efficiency of Stove Model I was 13 %. A second institutional stove was also design based on experience of initial test with the ricehusk stove and literature review. Stove Model II has overall efficiency about 12 % but very clean and continuous combustion. This stove was suitable for low temperature cooking process in very long period of operation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Biomass stoves